Evaluation of Social Security System Implementation for Indonesian Nurses in Saudi Arabia: A Case Study - Akhir Fahruddin; Slametiningsih Slametiningsih; Ade Koswara (Universitas Muhammadiyah Surakarta, 2022)
The employment social security administration or BPJS Ketenagakerjaan for Indonesian Migrant Workers (IMW) still leaves problems in the number of participation and socialization. This study aims to evaluate the implementation of social security system for Indonesian nurses in the Kingdom of Saudi Arabia. The research method was descriptive quantitative with a case study. The instrument used a CIPP Evaluation Model (Context, Input, Process, Products). There were 74 nurses as respondents and participated in the study. The indicators evaluated are membership, socialization, objectives program, benefit program and participation of the program. The results showed that 64.9% of respondents did not have BPJS membership (Context), 83.8% of respondents did not know the socialization of the BPJS program (Input), 66.2% of respondents did not know the purpose of the program and 60.8% of respondents did not know the benefits of the program (Process), while 86.5% of respondents were willing to participated in the BPJS program (Product). The conclusion of the study indicates the need for an evaluation of BPJS membership for Indonesian migrant workers, especially nurses in Saudi Arabia